2021
DOI: 10.1021/acs.est.1c02958
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Rare Earth Element Mobilization in a Mountain Watershed of the Colorado Mineral Belt with Concomitant Detection in Aquatic Biota: Increasing Climate Change-Driven Degradation to Water Quality

Abstract: In the western USA, one legacy of historic mining is drainage of acidic, metal-rich water generated by exposure to oxygen of sulfide minerals in mine workings, referred to as acid mine drainage (AMD). Streams receiving AMD and natural acid rock drainage (ARD) have a low pH, high dissolved metal concentrations, and extensive streambed oxide deposits. Recently, enhanced ARD generation in the Snake River watershed in the Rocky Mountains has been shown to be associated with warmer summer air temperatures, which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…In fact, Schwartzman & Volk (1989) estimated that without biogenic weathering, the earth would be tens of degrees warmer, than it is. However, through weathering, other chemical compounds might have become bioavailable (Rue & McKnight, 2021) that might have been harmful to organisms (Jones & Bennett, 2014; Vicca et al, 2022), such as aluminum which is a common companion in silica minerals (Amann et al, 2020). Aluminum is toxic to many organisms in the microgram per Litre range (Botté et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Schwartzman & Volk (1989) estimated that without biogenic weathering, the earth would be tens of degrees warmer, than it is. However, through weathering, other chemical compounds might have become bioavailable (Rue & McKnight, 2021) that might have been harmful to organisms (Jones & Bennett, 2014; Vicca et al, 2022), such as aluminum which is a common companion in silica minerals (Amann et al, 2020). Aluminum is toxic to many organisms in the microgram per Litre range (Botté et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the upper Snake River in the Colorado Rocky Mountains, USA, Todd et al (2012) observed significant increases in SO 4 and zinc (Zn) of ∼3 mg/L/yr and ∼30 μg/L/yr, respectively, during summer and fall from 1979 to 2011. Rue and McKnight (2021) reported a continuation of these trends through 2019, with associated increases in rare earth element concentrations. In the upper Elqui River basin in the Andes, north-central Chile, Flores et al (2017) identified significant upward trends in annual average SO 4 and copper (Cu) concentrations for several (though not all) sample sites of 1-10 mg/L/yr and <100-900 μg/L/yr, respectively, from 1990 to 2012.…”
Section: Introductionmentioning
confidence: 90%
“…The magnitude of concentration and load trend slopes at different sites were then compared to watershed characteristics associated with the different climate-linked causal mechanisms discussed above to identify correlations. The specific objectives of this study are to: (a) determine if the significant recent upward trends in solute concentrations observed in the upper Snake River (Rue & McKnight, 2021;Todd et al, 2012)…”
Section: 1029/2023wr036062mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as their use increases, so does their release into the environment due to anthropogenic activities. Recent studies have shown that mining, fossil fuel combustion, metallurgic processes, agriculture, technology processes and products, and sewage inputs are altering the natural abundance of REE in the terrestrial and marine environments. Moreover, the concentrations of REE in some ecosystems have shown increasing trends in the past decades. Slowly, humans are increasingly exposed to REE. , Nevertheless, there is a lack of studies on the fate, bioaccumulation, toxicity, and food web dynamics of REE, , hampering the estimation of potential human and ecological risks. REE are not typically included in environmental monitoring programs, and toxicity standards are still lacking.…”
Section: Introductionmentioning
confidence: 99%